Manifestations of State Sovereignty in Selective Immigration Policy: A Legal Analysis of the Implementation of the Clearance House Mechanism for Visa Calling Countries in Indonesia - Ryan Aditya; Marhaeni Ria Siombo (Indonesian Journal Publisher, 2026)
This study examines the manifestation of state sovereignty in Indonesia’s selective immigration policy through the implementation of the Clearance House mechanism for calling visa countries. Grounded in a normative juridical method employing statute and conceptual approaches, the research analyzes key legal instruments, including Law Number 6 of 2011 on Immigration and Regulation of the Minister of Law and Human Rights Number 2 of 2024, alongside the theoretical framework of sovereignty as articulated by Jean Bodin. The findings demonstrate that the Clearance House functions as a risk-based entry control mechanism that institutionalizes sovereign authority by integrating administrative, intelligence, and security considerations in visa decision-making. Through the Visa Assessment Coordination Team (TKPV), the state exercises its prerogative to filter foreign nationals based on IPOLEKSOSBUDHANKAM parameters, reflecting a shift from administrative governance toward security-oriented legal governance. However, the study also identifies critical challenges, particularly the broad discretionary power and subjective nature of risk assessment, which raise concerns regarding legal certainty, accountability, and potential arbitrariness. Therefore, strengthening standardization, transparency, and oversight mechanisms is essential to ensure that the exercise of state sovereignty remains consistent with the principles of legality, proportionality, and the rule of law in the context of increasing global mobility.